The Diversity, Distribution, and Habitat Preference of Rodents in Five Contrasting Habitats in the Tropical Rainforest of Malaysian Borneo - Raja-Azizi, Raja Nur Atiqah; Madinah, Adrus; Mohd-Azlan, Jayasilan (Tropical Natural History, 2023)
Rapid land-use changes may alter rodent assemblages in Malaysian Borneo. Understanding the diversity, distribution, and habitat preference of rodents from contrasting habitats may aid in pest control and conservation plan for rare species as well as species that important for conservation in Sarawak. In view of this, rodents were surveyed using cage and Sherman’s traps along several habitat gradients (primary forest, secondary forest, oil palm plantation, rural and urban areas) in Sarawak. This reveals that the highest species diversity was in the primary forest (H’=2.03) followed by the secondary forest (H’= 1.16), which decreased along the habitat gradient. Maxomys whiteheadi appeared as the indicator species in the primary forest (IndVal=0.894, p=0.033). Rattus tanezumi (n=155) appeared as the generalist followed by Sundamys muelleri (n=63) (PDI=0.61 and PDI=0.75, respectively). Meanwhile, three habitat specialists were detected (PDI=1.00), namely Leopoldamys sabanus, Maxomys surifer, and Niviventer rapit in the primary forest. Habitat preference analysis shows that most forest species were avoiding disturbed habitats and few species were recorded in disturbed habitats. This survey may provide information to aid various stakeholders in understanding rodent ecology for conservation purposes and pest control mitigation plans in Sarawak.